Nilai yang Dirasakan dan Harga terhadap Niat Pembelian Kembali dengan Mediasi Kepuasan Konsumen Sari Roti dan Moderasi Personal Selling - Ummi Rahmawati; Surya Bintarti; Ergo Nurpatria Kurniawan (Journal on Education, 2023)
Bread is the biggest staple food for Indonesian people, ranking third after rice and noodles. The data shows that Sari Roti within five years (2018-2022) has managed to occupy the first place in the top brand award. This study aims to examine the relationship between perceived value and price on repurchase intentions through the mediation of consumer satisfaction moderated by personal selling. The number of respondents in this study were 104 respondents who had purchased or consumed Sari Roti in the Bekasi Regency area. The taking of this population is non-probability sampling and the technique of taking respondents is purposive. This research was processed using a regression technique, in which the processing used SmartPLS 4 Software. This study proves 1) The perceived value of Sari Roti consumers can encourage repurchase intentions for Sari Roti products. 2) The prices set for Sari Roti products do not encourage consumers to intend to repurchase. 3). Sari Roti consumer satisfaction can mediate the perceived value of repurchase intention. 4) Consumer satisfaction can mediate the price set for Sari Roti products on repurchase intentions. 5) consumers who have a high level of satisfaction with Sari Roti products will encourage repurchase intentions. 6) Personal selling can play a role in strengthening the perceived value of Sari Roti consumers' repurchase intention. 7) Personal selling has a direct role on repurchase intention, so it cannot strengthen the price relationship on Sari Roti consumers' repurchase intention.